2015
DOI: 10.7196/sajch.2015.v9i4.913
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of the transfer of critically ill children to tertiary care in KwaZulu-Natal, South Africa

Abstract: Background.Obtaining care for an acutely ill child in specialised paediatric services relies on referral from lower-level facilities. In South Africa, it is common practice for acutely ill children to be transported far distances by non-specialist teams with limited equipment, knowledge and skills. Objectives. To describe the transfer of these children and to determine whether they deteriorate from the time of referral to the time of arrival at a tertiary centre. Furthermore, we sought to identify modifiable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 13 publications
(19 reference statements)
1
19
0
Order By: Relevance
“…Owing to this shortage, the transfer of critically ill neonates may occur frequently and often over vast distances. [5,6] In high-income countries, critical care transports (CCTs) of neonates are most often undertaken by specialised physician-based teams with additional training. This is not the case in SA, where emergency medical services (EMS) are responsible for all interfacility transfers (IFTs) regardless of the patient's condition, and it is likely to remain this way owing to a shortage of physicians [7] and specialist neonatologists.…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to this shortage, the transfer of critically ill neonates may occur frequently and often over vast distances. [5,6] In high-income countries, critical care transports (CCTs) of neonates are most often undertaken by specialised physician-based teams with additional training. This is not the case in SA, where emergency medical services (EMS) are responsible for all interfacility transfers (IFTs) regardless of the patient's condition, and it is likely to remain this way owing to a shortage of physicians [7] and specialist neonatologists.…”
Section: Researchmentioning
confidence: 99%
“…Consequently, many critical neonates may be transported by EMS personnel with very limited neonatal care experience and knowledge, as well as limited equipment capabilities. [5,6] Numerous international studies describe higher rates of adverse events and increased morbidity when neonates are transported by non-specialist units. Similarly, studies undertaken in SA have reported increased rates of adverse events.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Africa, it is common practice for children to be referred from lower-level facilities to higher-level facilities to access resources, specialist knowledge and skills for diagnosis and treatment. 12 Our South African experience shows the limited capacity to provide adequate care to complicated cases that present in the peripheral health service, as is evidenced by up to 34% mortality for these referrals within the first 24 h of admission to a tertiary facility. 13 There is a reliance on a referral system in the current South African public health care system due to centralisation for the provision of specialist paediatric and intensive care in tertiary institutions.…”
mentioning
confidence: 99%
“…13 There is a reliance on a referral system in the current South African public health care system due to centralisation for the provision of specialist paediatric and intensive care in tertiary institutions. 12 Due to the vast resource constraints and distances to be travelled in some regions of the country, appropriate and timely referral is quite difficult. 14 In conclusion, these patients generally have a poor prognosis depending on the severity of the cardiac and associated malformations.…”
mentioning
confidence: 99%